IMPLEMENTASI METODE FORWARD CHAINING UNTUK RANCANG BANGUN APLIKASI DAILY HAID BERBASIS MOBILE ANDROID - Cirebon, Rosidin; Sukarsa, Sukarsa; Mauliya, Nila Kholisotul; Sulaeman, Dicky Andika; Kohar, Abdul (LPPM UNU CIREBON, 2024)
Lack of knowledge and understanding of Muslim women on how to distinguish between female blood, such as menstruation and istihadhah causes difficulties in identifying the time of istihadhah, which can affect daily worship. This study aims to help Muslim women, especially female vocational school students, to more easily understand and distinguish between female blood types. Thus, they do not make mistakes in performing worship. This study was conducted on 35 female students of SMK NU Al Basyariyah Kedokan Bunder, who although they understand the legal basis of female blood, many of them still have difficulty distinguishing between menstruation and istihadhah. To provide guidance in accordance with Islamic law, an Android-based application called Daily Haid was created, using the forward chaining expert system method. To measure how effective and useful this application is, testing was carried out with the System Usability Scale (SUS) involving 30 respondents. The test results showed that the application scored 75, which placed it in the